Corpo e autonomia: repercussões da laqueadura na vida das mulheres - Menezes, Cláudio Munhoz Rozsanyi de (2016)
This paper discusses the repercussions of tubal ligation on women's lives, from how they, who have undergone surgical sterilization, process of cesarean in the municipality of Paranaguá/PR, perceived the changes arising from such surgery in their lives. To this end, semi-structured interviews were conducted with five women living in the municipality of Paranaguá. The data gathered were exposed in narrative format and organized in the following categories: tubal ligation process, perceptions of sexuality and prevention of STDs/HIV/AIDS. It has been observed, through data analysis, these women did not notice significant changes in their sexuality, prevention of STDs/HIV/AIDS was not an element of concern and/or relevance, presented certain difficulties in addressing sexuality itself on a man researcher and make no relationship between tubal ligation and the autonomy of their bodies. Were also discussed in this study the cultural elements that interfere on the categories mentioned, as well as family planning and benchmarks legal aspects of tubal ligation. It was concluded that, in Brazil, the cultural elements and violence in its various expressions, are presented as guiding deep these opinions and female attitudes, as well as also reflected in the attitude of legislators.